We eat dinner in the bathtub - Medearis, Angela Shelf, 1956-; Rogers, Jacqueline (New York : Scholastic, 1996)
A child visits a friend who lives in a topsy-turvy house.
270
RL 2. K-grade 2.
Accelerated Reader AR
Keywords: Dwellings -- Fiction; Humorous stories